Diffused reflectance measurements to detect tattoo ink location in skin using the crossover point. Issue 4 (11th February 2022) - Rudraiah, Pavitra Sokke; Duadi, Hamootal; Fixler, Dror
Abstract: Tattoos are highly trendy in western culture, but many people regret their tattoos for many reasons. It is essential to be aware of the ink location in advance to reduce the long and short‐term side effects. In this study, diffuse reflectance (DR) experiments were conducted on two‐layer (2L) tissue‐mimicking phantoms, where ink was sandwiched between the layers. An appreciable difference in the DR profile was found between the 2L phantom with and without the tattoo ink using the crossover point (Cp) method. Our technique was applied to ex vivo porcine skin. A point of intersection was found, between the skin and the tattooed skin. In the shorter wavelengths (500‐600 nm), a distinguishable 2L behavior was found, and in longer wavelengths (600‐850 nm), a single layer behavior was found between the tattooed skin before and after the intersection. In biological tissue, this Cp indeed finds the tattoo ink without harm to the surrounding skin. Abstract : Tattoos are highly trendy in western culture, but many people regret their tattoos for many reasons. It is essential to be aware of the ink location in advance to reduce the long and short‐term side effects. In this study, diffuse reflectance (DR) experiments were conducted on two‐layer (2L) tissue‐mimicking phantoms, where ink was sandwiched between the layers. An appreciable difference in the DR profile was found between the 2L phantom with and without tattoo ink using the crossover point (Cp) method.